(untitled) (Research, Society and Development, 2022)
Objective: to analyze the approved hospital admission authorization rates (AIH) for pneumonia, bronchitis and asthma in the 20th Decentralized Health Area of ​​Crato from January 2015 to December 2019 and to point out the relationship with the effectiveness of the health services provided in the city. Basic Attention. Methods: descriptive, retrospective and documentary research, with a quantitative approach carried out in the second half of 2019. Hospital records, available in the SUS Hospital Information System (SIH/SUS), from January 2015 to December 2019 and regarding the approved Hospital Admissions Authorizations (AIH). The information selected for the present study was related to AIH due to pneumonia, asthma and bronchitis in the municipalities that are part of the 20th Decentralized Health Area of ​​Crato. Results: 17.5% increase in AIHs due to pneumonia, 0.6% increase due to bronchitis and 2.1% decrease in AIHs due to asthma. Conclusion: The measures aimed at reducing smoking in the population, despite having been successful in reducing the habit of smoking, were not enough to guarantee the reduction of the rates of AIH’s approved for the three pathologies studied. It is suggested as measures the strengthening of Primary Care, the increase in taxation on the production and sale of cigarettes, as well as an increase in the facilitation of drug dispensing and the obligation of the physical education professional in the composition of the PHC teams.